Graphical simulation suite for a robotic manipulator - Tan, Boon Yaw. (2008)
Robots have been widely used for industrial applications. Some of these examples are electronics components assembly, material handling, spot welding, spray painting, remotely piloted vehicles, die casting, forging, grinding, deburring, tending machine tools, molding in the plastics industry, applying sealants to motor car windscreens, arc welding and surgical operations.